'The totalitarian destruction of the public sphere?' Newspapers and structures of public communication in socialist countries: the example of the German Democratic Republic. (September 2015) - Fiedler, Anke; Meyen, Michael
Using the example of the former German Democratic Republic (GDR), this study deals with the public sphere in Eastern European countries before 1989. It supports the thesis that even the 'guided' and controlled daily press enabled the readers (even in a limited way) to observe the process of communication and to make up their own minds. The article is based on two main sources: files from the Federal archives in Berlin and a series of 100 biographical interviews, held between 2000 and 2002, in which former GDR residents have been asked about their everyday media usage during the 1980s. This article discusses the concept of public communication and propaganda and shows how the politically staged public sphere operated from the point of view of the rulers and professional readers as well as regular subscribers.